Prevalence and morphology of middle mesial canals in a group of Thai permanent mandibular molars from cone-beam computed tomography images - Arayasantiparb, Raweewan; Wanichwetin, Watinee; Banomyong, Danuchit (Mahidol Dental Journal, 2020)
Objective: To determine prevalence and morphology of middle mesial (MM) canals in a group of Thai permanent mandibular first and second molars by using cone-beam computed tomography (CBCT). Materials and Methods: CBCT images with a voxel size of 0.125 mm and field of view of 60 x 60 mm of 903 mandibular first and second molars from 595 Thai patients were examined. MM canals were classified as either confluent or independent type; fin (isthmus) type was not included. MM canal must have its own orifice within range of 1 mm from orifice level, with continuous canal at least half of root length. Presence and morphology of MM canals were recorded. Distances from MM canal to MB and ML canals were measured as well as the thinnest dentin thickness on furcal and mesial sides of MM canals. Results: In overall, MM canals were found in 0.22% (2/903). Both MM canals were found in mandibular first molars (0.4%; 2/518). One was independent type, and the other was confluent type that joined with MB canal. Conclusion: According to the classification, MM canals in this Thai population were very rare and detected only in mandibular first molars as either confluent or independent type.